The physiological effects of slow breathing in the healthy human. Issue 4 (December 2017) - Russo, Marc A.; Santarelli, Danielle M.; O'Rourke, Dean
Slow breathing practices have been adopted in the modern world across the globe due to their claimed health benefits. This has piqued the interest of researchers and clinicians who have initiated investigations into the physiological (and psychological) effects of slow breathing techniques and attempted to uncover the underlying mechanisms. The aim of this article is to provide a comprehensive overview of normal respiratory physiology and the documented physiological effects of slow breathing techniques according to research in healthy humans. The review focuses on the physiological implications to the respiratory, cardiovascular, cardiorespiratory and autonomic nervous systems, with particular focus on diaphragm activity, ventilation efficiency, haemodynamics, heart rate variability, cardiorespiratory coupling, respiratory sinus arrhythmia and sympathovagal balance. The review ends with a brief discussion of the potential clinical implications of slow breathing techniques. This is a topic that warrants further research, understanding and discussion. Key points: Slow breathing practices have gained popularity in the western world due to their claimed health benefits, yet remain relatively untouched by the medical community. Investigations into the physiological effects of slow breathing have uncovered significant effects on the respiratory, cardiovascular, cardiorespiratory and autonomic nervous systems. Key findings include effects on respiratory muscle activity, ventilation efficiency, chemoreflex and baroreflex sensitivity, heart rate variability, blood flow dynamics, respiratory sinus arrhythmia, cardiorespiratory coupling, and sympathovagal balance. There appears to be potential for use of controlled slow breathing techniques as a means of optimising physiological parameters that appear to be associated with health and longevity, and that may extend to disease states; however, there is a dire need for further research into the area. Educational aims: To provide a comprehensive overview of normal human respiratory physiology and the documented effects of slow breathing in healthy humans. To review and discuss the evidence and hypotheses regarding the mechanisms underlying slow breathing physiological effects in humans. To provide a definition of slow breathing and what may constitute "autonomically optimised respiration". To open discussion on the potential clinical implications of slow breathing techniques and the need for further research. Slow breathing techniques have been used in asthma but are there effects in healthy individuals? http://ow.ly/gCPO30eQOPZ